Water Treatment Methods for Mineral Processing Operations - Guerra Rodriguez, Hugo Alejandro (Curtin University, 2023)
The scarcity of clean water in many mineral processing plants in Australia and around the world is well documented. The availability of suitable process water has been a bottle-neck for expansion of several operations due to high cost associated with water purification. In this study, desalination alternatives for bore water sourced from the Laverton region of Western Australia were assessed to produce fit-for-purpose water in mineral processing activities. These options included precipitation, nanofiltration, and electrodialysis.